Chewing lice of the genus Myrsidea (Phthiraptera: Menoponidae) from the Cardinalidae, Emberizidae, Fringillidae and Thraupidae (Aves: Passeriformes) from Costa Rica, with descriptions of four new species - Kounek, Filip; Sychra, Oldrich; Capek, Miroslav; Lipkova, Alexandra; Literak, Ivan (Zootaxa, 2011)
A total of 376 individuals of 35 bird species belonging to the families Cardinalidae, Emberizidae, Fringillidae, and Thraupidae were examined for chewing lice in Costa Rica in 2004, 2009 and 2010. A total of 128 birds of 19 species were parasitised with 17 species of Myrsidea. Descriptions and illustrations are given for four new species of Myrsidea. These new species and their type hosts are: Myrsidea bidentata ex Piranga bidentata (Cardinalidae), M. dolejskae ex Arremon brunneinucha (Emberizidae), M. roubalovae ex Ramphocelus sanguinolentus (Thraupidae), and M. rubica ex Habia rubica (Cardinalidae). Records of new host-louse associations are: Chlorospingus ophthalmicus (Emberizidae) and Euphonia hirundinacea (Fringillidae) for M. violaceae, Ramphocelus costaricensis (Thraupidae) for M. fusca, and Tangara dowii (Thraupidae) for M. bonariensis. Records of ten other louse species of the genus Myrsidea from birds belonging to these families are also presented and discussed.